Functional analysis of membrane contact sites in C. elegans early embryogenesis - Jeyasimman, Darshini (Nanyang Technological University, 2021)
SMP proteins transport lipids from one membrane compartment to another at membrane contact sites via their lipid harboring SMP domains. In my thesis project, I used C. elegans early embryos to investigate the physiological functions of SMP proteins in cellular lipid homeostasis. The data presented in my thesis provides strong evidence to the model, whereby some of the SMP proteins act at endoplasmic reticulum (ER)-endosome contacts and contribute to the maintenance of cellular PI(4,5)P2 homeostasis together with PI(4,5)P2 phosphatases. Furthermore, I present additional data that suggests that ESYT-2 (one of the SMP proteins) localizes to ER-plasma membrane contacts in C. elegans, although physiological functions of ESYT-2 at these contacts remain elusive. Collectively, my studies suggest that the functions of SMP proteins are critical for normal development of C. elegans.